2002
DOI: 10.1007/s004060200013
|View full text |Cite
|
Sign up to set email alerts
|

Serum paraoxonase activity changes in patients with Alzheimer's disease and vascular dementia

Abstract: The prevalence of Alzheimer's disease (AD) and vascular dementia (VAD) increases with aging of the population. The role of lipoproteins in the pathogenesis of AD is unclear: apoE(2) offers protection and apoE(3) is neutral, while apoE(4) promotes the development of the disease. Recently, several studies have confirmed the role of oxidative stress in the pathogenesis of AD and VAD. HDL-associated paraoxonase is one of the antioxidative enzymes that may reduce LDL oxidation. In our study, we investigated the lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
62
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 32 publications
6
62
1
1
Order By: Relevance
“…Despite reports (16,23,(25)(26)(27)(44)(45)(46) on the preferential loss of paraoxon-hydrolyzing activity in serum of persons with oxidative stress-associated pathological signs, there have been no reports concerning causes for the preferential loss of paraoxonase activity. Even the substrate-dependent polymorphism could not account for the preferential reduction of serum paraoxonase activity in cardiovascular disease patients versus controls (21,47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite reports (16,23,(25)(26)(27)(44)(45)(46) on the preferential loss of paraoxon-hydrolyzing activity in serum of persons with oxidative stress-associated pathological signs, there have been no reports concerning causes for the preferential loss of paraoxonase activity. Even the substrate-dependent polymorphism could not account for the preferential reduction of serum paraoxonase activity in cardiovascular disease patients versus controls (21,47).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the substrate-specific feature of PON1 may be seen in the substrate-dependent alteration of serum PON1 activity in cardiovascular disease patients; the serum paraoxonase activity decreased significantly ( ‫ف‬ 20%), in contrast to no change of serum arylesterase activity (21)(22)(23). Likewise, such a preferential decrease of paraoxonase activity has been demonstrated in some oxidative stress-associated diseases such as hypercholesterolemia, di-abetes mellitus, or Alzheimer's disease (24)(25)(26). The same phenomenon was also observed with smoking or advancing age, in which oxidative stress was predominant (8,27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One population based study of African Americans has shown that higher serum cholesterol is associated with increased risk of AD in APOE4 negative subjects, but not in those carrying at least one ε4 allele [61]. Many case -control studies have also confirmed that mild hypercholesterolemia accompanies late-onset AD [49,62,63]. However, a 32-year long follow-up study of 1462 women has failed to find an association of mid-life hypercholesterolemia with increasing risk of AD, and even some studies have indicated that a high blood cholesterol especially in latelife is actually protective against AD [64,65,66].…”
Section: Metabolic Risk Factors Of Ad: Present Statusmentioning
confidence: 99%
“…It was noted in several studies that there was no relation between dementia and PON1 (95)(96)(97)(98). Similarly, PON1 activity was reported to drop in Alzheimer's patients, although the results are contradictory (99)(100)(101). Dantoine et al argued that the 192 PON1 polymorphism might be a critical marker in distinguishing Alzheimer's patients from patients with vascular dementia and healthy individuals (96).…”
Section: Clinical Significancementioning
confidence: 99%